1975
DOI: 10.2134/agronj1975.00021962006700060014x
|View full text |Cite
|
Sign up to set email alerts
|

N Behavior Under No‐Till vs. Conventional Corn Culture. I. First‐Year Results Using Unlabeled N Fertilizer1

Abstract: This study comparing corn yields from different rates of applied N under no‐tillage and conventional culture was prompted by numerous field observations in Maryland that no‐till corn, with low to moderate rates of N, often showed more pronounced N deficiency symptoms than did conventionally tilled corn. Little is known regarding the relative N requirements of untilled corn grown in cover‐crop residues as compared to conventional tillage. The purpose of this study was therefore, to determine whether tillage met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 1 publication
2
13
2
Order By: Relevance
“…This is contrary to suggestions by Thomas et al (1973), Bandel et al (1975) and Moschler and Martens (1975), who indicated that increased N fertilizer application rates were necessary for no-till to achieve yields equivalent to conventional tillage (plow). However, Thomas and Frye (1984) indicated that N requirements for plants grown under conventional tillage and no-till were similar if yields were similar.…”
Section: Introductioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This is contrary to suggestions by Thomas et al (1973), Bandel et al (1975) and Moschler and Martens (1975), who indicated that increased N fertilizer application rates were necessary for no-till to achieve yields equivalent to conventional tillage (plow). However, Thomas and Frye (1984) indicated that N requirements for plants grown under conventional tillage and no-till were similar if yields were similar.…”
Section: Introductioncontrasting
confidence: 87%
“…These data indicated that the water conservation potential of reduced-tillage practices was not sufficient to improve maize yield. Also, contrary to some earlier reports (Thomas et al, 1973;Bandel et al, 1975;Moschler and Martens, 1975), it does not appear that, in this climatic zone, maize produced without tillage requires more N fertilizer. "LAD (M) has units of modified growing degree days ( "C day).…”
Section: Introductioncontrasting
confidence: 75%
“…surprising because of a transient yet significant N deficiency which lowers crop yields in recently established NT systems (Bandel et al, 1975;Blevins et al, 1977;Rice et al, 1986;Vetsch & Randall, 2000). This observed N deficiency has been associated with increased N 2 O-emissions in NT systems (Burford et al, 1981;Rice & Smith, 1982;Linn & Doran, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…At some locations, decreased availability of soil N was associated with a loss of crop yield. In other studies lacking labeled fertilizer, symptoms of N deficiency were more evident in no-tilled crops than with conventional tillage (Thomas et al, 1973;Bandel et al, 1975). To date the effects of notillage on the chemical nature of SOM have received little attention.…”
Section: No-tillage In Temperate Climatesmentioning
confidence: 95%